A Study of Translated Matrimonial Shar'i Court Documents from Arabic into English: The Case of Palestine - Khalaf, Camellia Najeh Abdelkarim (2023)
Translating sharia court legal documents is one of the most challenging tasks for translators due to the effort needed to convey accurate and exact meanings of legal and Islam-driven terms. In this study, the analytical descriptive method is used to analyze matrimonial documents in order to explore the problems which confront Palestinian sworn translators in sharia court documents, to identify similarities and differences between Arabic legal system and English legal system, to assess the translation procedures used by the translators in dealing with terminologies in terms of accuracy and acceptability, and to find out how the translators deal with linguistic and translational decision in translating religious expressions in legal documents of sharia court. In doing so, Searle’s speech act classifications, Venti’s model, and Vinay and Darbelnet’s model of translation are used. The findings reveal that speech act similarities and differences between the Arabic legal system and the English legal system in matrimonial Sharia court documents are mainly related to the use of modal verbs, conditional sentences, the use of active and passive voice, and the use of verb tense. It is found that equivalence, literal, borrowing and modulation are found to be more accurate and acceptable in most of the translations of matrimonial documents terminologies. It is also found that the speech acts force is affected by the translators’ mishandling of language norms and translation norms